Novel compound heterozygous mutations of LAMA2-limb–girdle muscular dystrophy: A case report and literature review - Wang, Duo-Zi; Li, Bing-Hu; Ma, Qiong; Yu, Zhou; Chen, Kai; He, Ying; Tan, Song (Frontiers in Neurology, 2023)
The laminin α2 (LAMA2) gene pathogenic variants can lead to limb–girdle muscular dystrophy (known as LGMDR23), which is rarely reported and characterized by proximal weakness in the limbs. We present the case of a 52-year-old woman who gradually developed weakness in both lower extremities since the age of 32 years. Magnetic resonance imaging (MRI) brain showed symmetrical sphenoid wings-like white matter demyelination in bilateral lateral ventricles. Electromyography showed quadriceps muscle damage on the bilateral lower extremity. Next-generation sequencing (NGS) found two loci variations in the LAMA2 gene, i.e., c.2749 + 2dup and c.8689C>T. This case highlights the importance of considering LGMDR23 in patients presenting with weakness and white matter demyelination on MRI brain and further expands the gene variants spectrum of LGMDR23.